Information Handling - Rich, R. P. (Methods of Information in Medicine, 1965)
This paper explains how a small research effort in document retrieval led to the development of a generally useful package of information processing programs, first for a small (IBM 1401) computer and then for a large (IBM 7094) computer, to meet the growing demand, The approach is based ori standard programs for routine operations (editing, printing, searching) on information files, supplemented by a problem-oriented computer language for programming those tasks which the standard ‘ programs will not handle.The entire package has been carefully designed so that it can easily be taught to and used by people without previous computer experience, including clerical staff.